Practical Plants Classification using Framing to Reduce Cognivite Load of High School Students - Septiana, Rosinta; Rahmat, Adi; Hidayat, Topik (Universitas Sebelas Maret, 2015)
This study was conducted to reduce the cognitive load of high school students in a classification plant laboratory. The subjects were students of class X IPA one of private high school Favorite in Bandung, divided into experimental class (36 students) and control class (36 students). The experimental class used Framing for practical activities providing dikotomous key scheme, while the control class practical activities carried out in accordance used worksheet conventionally . Cognitive load was measured by looking at differences in the students' ability to receive and process information (information processing), mental effort and learning outcomes in the form of reasoning ability of students in the classification of plants. Data ability to receive and process information captured by task complexity combined worksheet on the worksheet students. Data captured by the mental effort of subjective rating scale questionnaire Likert scale-based, while the data captured using the reasoning ability of students to write test questions based on indicators describing complex thinking. Data were analyzed by using a different test and the average correlation between the three components of cognitive load. The analysis showed both the experimental class and the control class relationship between the ability to accept the reasoning ability showed a positive correlation, while the relationship between mental effort with reasoning abilities showed a negative correlation. These results illustrate the cognitive load balancing character students in practical activities in both classes of plant classification research. However, students in the experimental class has the ability to receive and process information that is higher and significantly different than the control class. Instead the experimental class mental effort value lower than the control class, showed that the cognitive load of students in the experimental class lower than the cognitive load control class. In other words, the use of framing the practical activities of classification of plants in the experimental class has been able to decrease the cognitive load of students.Kata kunci: beban kognitif, praktikum klasifikasi tumbuhan, framing